Clinical effectiveness of non-invasive selective cryolipolysis. (October 2014) - Kim, Jiehoon; Kim, Dai Hyun; Ryu, Hwa Jung
Abstract: Background: Excess subcutaneous fat causes not only cosmetic issues, but also substantial systemic health problems. Cryolipolysis has been reported to provide non-invasive fat reduction that significantly reduces subcutaneous fat cells with controlled, localized cooling. Objective: This study is intended to determine whether a cryolipolysis device can effectively reduce subcutaneous fat without damaging the overlying skin or causing significant side effects and ultimately produce improved cosmetic results. Materials and methods: A total of 15 patients participated in this study and they were treated unilaterally in a split-body trial manner with a non-invasive cryolipolysis device (Micool ™, Hironic Co., Seongnam, Korea). The degree of improvement was assessed by both objective and subjective assessments. Complications and side effects were recorded at every visit. Results: The results of both objective and subjective assessments showed significant improvements in subcutaneous fat reduction without any meaningful complications. Conclusion: Non-invasive selective cryolipolysis has been reported to be a safe and effective treatment modality for the reduction of excess adipose tissue. Therefore, cryolipolysis is a promising technology that could be an appropriate and safe therapeutic option for subcutaneous fat reduction.